Pelatihan Soft-Skill Public Speaking Pada Mahasiswa Program Studi Ilmu Pemerintahan FISIP Universitas Halu Oleo - Lestari, Dian Trianita; Saputri, Shinta Arjunita; Arwih, Muhammad Zaenal; Samiruddin T. (Indonesian Journal of Community Services, 2023)
The Community Service Program with the title: Soft-Skill Public Speaking Training for Government Science Study Program Students, FISIP Halu Oleo University, aims to improve students' speaking skills, particularly in front of audiences. This is critical for preparing graduates to compete in the labor market. As a result, the service team conducted Soft-Skill Public Speaking training activities by presenting material that needed to be mastered in Public Speaking. Students are directed to directly compose speeches at the end of the training, which is displayed in video form and uploaded via the YouTube video-sharing medium. Finally, this training was able to solve the problems encountered by Government Science Study Program Students as service objects as indicated by service participants' speaking ability that has significantly improved, as evidenced by good pronunciation and intonation.